Alternative low-cost approach to the synthesis of magnetic iron oxide nanoparticles by thermal decomposition of organic precursors - Perez de Berti, Ignacio Omar (2013)
A new approach to thermal decomposition of organic iron precursors is reported, which results in a simpler and more economical method to produce well crystallized γ-Fe2O3 nanoparticles (NPs) with average sizes within the 3-17 nm range. The NPs were characterized by TEM, SAED, XRD, DLS-QELS, Mössbauer spectroscopy at different temperatures, FT-IR and magnetic measurements. The obtained γ-Fe2O3 NPs are coated with oleic acid and, in a lower quantity, with oleylamine (about 1.5 nm in thickness). It was shown that changing operative variables allows us to tune the average particle diameters and obtain a very narrow or monodisperse distribution of sizes. The γ-Fe2O3 NPs behave superparamagnetically at room temperature and their magnetization saturation is reduced by about 34% in comparison with bulk maghemite. The results indicate that the distance between two neighbour NPs, generated by the coating, of about 3 nm is insufficient to inhibit interparticle magnetic interactions when the average diameter is 8.8 nm. The good quality of the NPs, obtained through the present low-cost and easy-handling process, open a new perspective for future technological applications.